PENGARUH KOMPETENSI AUDITOR DAN PENGALAMAN AUDITOR TERHADAP KUALITAS AUDIT DENGAN KECERDASAN SPIRITUAL SEBAGAI VARIABEL MODERATING - Saida, Elisabet (Soetomo Accounting Review, 2022)
The purpose is a) To Analyze and prove the effect of auditor competence on audit quality.b) To Analyze and prove the effect of the auditor’s experince on audit quality c)To analyze spirituyal intellegence is abale to moderate the effect of auditpr competence on audit quality.d) To analyze and prove spiritual intellegence is abale to moderate the effect on the auditor’s experience on audit quality.This study uses a quantitative aproach. Populatin in this study are all independent auditors who work at public accountiong firms. While the sample used 10 public accountiong firms in surabaya.This study use a questionnaire.The test conducted is the moderating regresion analysis test. The research result obtained a)Auditor competence affect audit quality.b) Auditor experience affect audit quality.c) Spiritual intelegence moderates the effect of auditor competence on audit quality.d) Spiritual intelegence does not moderate rge effect of audit experience on audit quality.